2014
DOI: 10.1155/2014/819871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Heart Rate Variability: A Systematic Review

Abstract: Aim. To summarize all relevant trials and critically evaluate the effect of acupuncture on heart rate variability (HRV). Method. This was a systematic review with meta-analysis. Keyword search was conducted in 7 databases for randomized controlled trials (RCTs). Data extraction and risk of bias were done. Results. Fourteen included studies showed a decreasing effect of acupuncture on low frequency (LF) and low frequency to high frequency ratio (LF/HF ratio) of HRV for nonhealthy subjects and on normalized low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 26 publications
1
24
1
3
Order By: Relevance
“…Animal studies suggest that auricular acupuncture activates g-aminobutyric acid receptors, which reduces symptoms of morphine withdrawal, 16 and there is support for the hypothesis that opioid release stimulated by acupuncture helps to restore the release of dopamine. 17 In particular, auricular acupuncture potentially modifies autonomic dysfunction by increasing parasympathetic activity 18 and reduces sympathetic hyperactivity, 19 and stimulation of the liver 3 acupuncture point (LR 3; Tai Chong) activates several cortical and subcortical regions responsible for acute and chronic pain. 20 Recently, acupuncture treatment has been described as effective and safe in children 21 and newborns.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Animal studies suggest that auricular acupuncture activates g-aminobutyric acid receptors, which reduces symptoms of morphine withdrawal, 16 and there is support for the hypothesis that opioid release stimulated by acupuncture helps to restore the release of dopamine. 17 In particular, auricular acupuncture potentially modifies autonomic dysfunction by increasing parasympathetic activity 18 and reduces sympathetic hyperactivity, 19 and stimulation of the liver 3 acupuncture point (LR 3; Tai Chong) activates several cortical and subcortical regions responsible for acute and chronic pain. 20 Recently, acupuncture treatment has been described as effective and safe in children 21 and newborns.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Although the current study did not show this type of results, the tendency showed a parallel to this previous work. Acupuncture modulation of HRV has been proven by a meta-analysis, which suggested that the LF but not the HF component could be modulated25. Thus, acupuncture can modulate the ANS by activating the sympathetic and parasympathetic nervous systems.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been shown to influence the central nervous system21 and the functional status of the ANS in humans2223 and laboratory animals24. Acupuncture has also been shown to be effective in modulating HRV, although there was not sufficient evidence to determine if HRV could be an indicator of the therapeutic effect of acupuncture25.…”
mentioning
confidence: 99%
“…Für die Akupunkturforschung gewann die Analyse der Herzratenvariabilität (HRV) in den letzten Jahren zunehmend an Bedeutung [1]. Das menschliche Herz schlägt in einem variablen Rhythmus, der primär vom vegetativen Nervensystem vorgegeben wird.…”
Section: Einführungunclassified
“…In einem kürzlich publizierten Review zu Akupunktur und HRV [1] zeigten 14 Studien homogene Resultate, mit einer durchgehenden Erhöhung der hohen Frequenzanteile (HF) und einer Senkung des Verhältnisses zwischen niedrigen- und hohen Frequenzanteilen (LF:HF), sowohl bei Kranken wie auch bei Gesunden. Doch nicht bei allen Studien kam es zu den gleichen Resultaten.…”
Section: Diskussion Und Schlussfolgerungunclassified